Therapeutic Touch in Exercise Videos: A Randomized Experiment of the Impact on the Evaluation of Therapists' Competence and Viewers' Self-Reliance - Bientzle, Martina; Minje, Janina; Cress, Ulrike; Kimmerle, Joachim (Frontiers in Sports and Active Living, 2019)
From a psychological health perspective, being physically touched is highly relevant throughout people's lives. Touch plays an important role in many contexts, such as in instructing movement exercises. Exercise videos have become a well-accepted format to support therapists in instructing movement exercises. In the study presented here we examined the impact of the use of therapeutic touch in exercise videos on people's evaluation of physiotherapists' competence and on their own self-reliance. In a between-group randomized experiment, 125 participants watched one of three videos that showed a physiotherapist who instructed a movement exercise to a patient. The physiotherapist touched the patient during the treatment (therapist-touch, TT), instructed the patient to use self-touch (ST), or provided only exercise instruction without physical touch (no-touch, NT). In the TT condition, the participants' perception was that the physiotherapist exhibited more professional competence. However, participants considered the movement exercise in this TT condition to have less potential for fostering their autonomy. Finally, participants in the ST condition had the biggest increase in perceived self-efficacy. The way of touching a patient in an exercise video influences the perception of the treatment. We conclude that therapeutic touch should be applied in exercise videos in a goal-oriented way: It seems appropriate to use ST if the aim is to strengthen viewers' self-reliance and to use TT to arouse trust in the competence of the therapist.